2018
DOI: 10.1089/end.2018.0304
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Kidney Stone Composition Within the United States

Abstract: Kidney stone composition does not vary widely by region within the United States. Although temperature and humidity play a role in stone incidence, there does not appear to be a large variation between different climates, with the exception of uric acid stone formation in Florida.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…This introduced a big bias because uric acid stone might occur as a second dominant one, and it should be counted in the uric acid group. Dahllite and ammonium magnesium phosphate hexahydrate also account for a big part of stones [9]. However, these stones were excluded from their study.…”
Section: Discussionmentioning
confidence: 99%
“…This introduced a big bias because uric acid stone might occur as a second dominant one, and it should be counted in the uric acid group. Dahllite and ammonium magnesium phosphate hexahydrate also account for a big part of stones [9]. However, these stones were excluded from their study.…”
Section: Discussionmentioning
confidence: 99%
“…Although the most common composition of calculi is of calcium oxalate and calcium phosphate (82.8% in 2015) in Japan [2], which is comparable to those in the United States [24], the performance of our model for patients of other ethnicities is unknown. Further validation outside of Japan is necessary.…”
Section: Study Limitationsmentioning
confidence: 99%
“…A narrative review of the estimated prevalence of uric acid nephrolithiasis around the world demonstrated that higher rates were observed in countries with hot and dry climates [7]. In a study comparing the composition of urinary stones from seven areas of the United States, a higher frequency of uric acid stones was observed in Florida, one of the states with the highest average temperature and humidity [8].Furthermore, a recent study showed that the risk of acutely emergent stone episodes after exposure to short periods of high wet-bulb temperatures was higher in men who form uric acid stones more frequently than in women [9]. Consequently, the effect of climate on the risk of uric acid stones could be related to relatively short heath events ("heath waves") rather than to the increase in average temperature.…”
Section: Introductionmentioning
confidence: 99%